Pengaruh Food Quality dan Atmosphere terhadap Customer Loyalty dengan Customer Satisfaction Sebagai Variabel Intervening Pada Café Intro di Surabaya - Hendra Winarjo (Jurnal Strategi Pemasaran, 2017)
The study discusses the influence of food quality andatmosphere on customer loyalty with customer satisfaction as anintervening variable at Café Intro in Surabaya. The sample ofthis research is 100 Café Intro customers who purchase inOctober 2016-March 2017. Measurements are done from foodquality (X1) with presentation indicator, variety menu, healthoptions, taste, freshness, temperature. Atmosphere (X2) withindicator of style, layout, color, lighting, furnishing, ambience,customer satisfaction variable (Y1) withsatisfaction asfulfillment indicator, satisfaction as pleasure, satisfaction asambivalence, while customer loyalty (Z1) Recommend friends,continue purchasing. The results showed: (1) Food quality hassignificant effect on customer satisfaction; (2) Atmosphere has asignificant effect on customer satisfaction; (3) customersatisfation has a significant effect on customer loyalty.